2008
DOI: 10.1590/s0103-84782008005000098
|View full text |Cite
|
Sign up to set email alerts
|

Amostragem, caracterização de sintomas e escala diagramática da mancha graxa dos citros (Mycosphaerella citri) no Recôncavo Baiano

Abstract: O Recôncavo da Bahia é uma região de clima propício à mancha graxa dos citros (Mycosphaerella citri), doença nunca antes estudada no Brasil. Os objetivos deste trabalho foram definir o tamanho mínimo de amostra para quantificar a incidência, caracterizar os sintomas da doença e elaborar uma escala diagramática para a avaliação de sua severidade. A partir de uma amostragem piloto realizada por avaliação de cinco folhas por quadrante, quatro quadrantes por planta e 30 plantas em cada um dos 10 pomares visitados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 2 publications
3
11
1
Order By: Relevance
“…In Recôncavo Baiano, CGS is highly prevalent with high incidences (Silva et al, 2009), and the same pattern was observed in the experimental groves. Prevalence, plant incidence and leaf incidence for both cultivars were not different from that described by Silva et al (2009) andSilva (2008).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…In Recôncavo Baiano, CGS is highly prevalent with high incidences (Silva et al, 2009), and the same pattern was observed in the experimental groves. Prevalence, plant incidence and leaf incidence for both cultivars were not different from that described by Silva et al (2009) andSilva (2008).…”
Section: Discussionsupporting
confidence: 75%
“…In fact, there are no reports about damage or losses in Brazil. Nevertheless, Silva et al (2009) show that in Recôncavo Baiano, CGS can be found in every single sampled grove at an incidence of 100% of the sampled plants. Besides that, Silva (2008) reported the proportion of symptomatic leaves varying from 0.77 to 0.96 over 15 monthly evaluations of 300 plants in ten groves.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations